'What is (mental) disease?': an open letter to Christopher Boorse. Issue 2 (1st April 2001) - Fulford, K W M
Abstract : This "open letter" to Christopher Boorse is a response to his influential naturalist (value-excluding) analysis of disease from the perspective of linguistic-analytic value theory. The key linguistic-analytic point against Boorse (and other naturalists) is that, although defining disease value free, he (and they) continue to use the term with clear evaluative connotations. A descriptivist (value-entailing) analysis of disease would allow value-free definition consistently with value-laden use: but descriptivism fails when applied to mental disorder because it depends on shared values whereas the values relevant to mental disorders are highly diverse. A part-function analysis, similarly, although initially persuasive for physical disorders, fails with the psychotic mental disorders because these, characteristically, involve disturbances of the rationality of the person as a whole. The difficulties encountered in applying naturalism to mental disorders point, linguistic-analytically, to the possibility that there is, after all, an evaluative element of meaning, deeply hidden but still logically operative, in the concept of disease.